HBsAg and anti-HCV screening in elderly hospitalized patients of a German tertiary referral centre - Kant, J.; Kratzsch, J.; Maier, M.; Liebert, U. G.; Berg, T.; Wiegand, J. (Zeitschrift für Gastroenterologie, 2016)
Background: Elderly patients are under-represented in hepatitis B and C screening approaches, but may be at increased risk for advanced liver disease. We therefore screened a hospitalized elderly population.Materials and methods: 6011 admissions to the department of internal medicine and neurology within one year were screened for HBsAg and anti-HCV (Elecsys®-HBsAg and -anti-HCV). Positive anti-HCV results were confirmed with the INNO-LIA™ assay. HCV-RNA was analyzed by real-time PCR in the case of confirmed positive anti-HCV results, HBV-DNA in the confirmed HBsAg positive individuals.Results: Patient´s mean age (62.4 years) was 19 years above that of the average German population. The confirmed HBsAg prevalence was 0.6 %. 34 % (n = 12/35) of HBsAg positive cases were newly diagnosed, three of them presented with HBV-DNA levels > 2000 IU/mL. The confirmed anti-HCV prevalence was 0.9 %. 14 % (n = 8/56) of anti-HCV positive patients were previously undiagnosed. HCV-RNA was positive in three of them. In newly diagnosed individuals cirrhosis was present in 1/12 of the HBsAg and in 3/8 of the anti-HCV positive individuals. Compared to non-infected controls, the following risk factors were significantly more frequent in infected patients: (i) HBsAg: sexual exposure (20 % vs. 2 %), blood transfusion before 1992 (13 % vs. 6 %), referrals from nursing homes (10 % vs. 1 %). (ii) Anti-HCV: blood transfusion before 1992 (41 % vs. 6 %), IVDU (25 % vs. 0.5 %), organ transplantation (20 % vs. 5 %), hemodialysis (11 % vs. 3 %).Conclusions: HBsAg and anti-HCV were underdiagnosed in a senescent population, however, only few cases presented with advanced liver disease. Referrals from nursing homes were at increased risk for HBV infection.
Keywords: ältere Patienten; direkt antiviral wirksame Substanzen; Hepatitis B; Hepatitis C; Zirrhose